(untitled) (Research, Society and Development, 2024)
Nootropics are drugs that belong to the class of natural or synthetic substances used to improve cognitive functions. They are used to treat memory problems, Attention Deficit Disorders and Alzheimer’s. For various reasons, there has been a significant increase in people using these medications off-label. The main objective of the study was to map side effects and reveal social and academic impacts, by reported prevalence, of off-label use of nootropics and to outline the sociodemographic profile of this population. This is a quantitative-qualitative study using multimethods approved by the Research Ethics Committee. The collected data was analyzed and presented in statistical models and content analysis. The research had the participation of 299 university students, the majority of whom were female; white race and health sciences students. The results indicate that 29.4% of participants use nootropics, associated with academic life, with the aim of improving concentration. Of those who use medication, 91.03% report experiencing side effects such as anxiety, insomnia, dry mouth and tremors and do not express consistent positive effects in relation to academic improvement. The evidence indicates the need for greater attention, psychosocial and pedagogical support for young university students in the academic space and the implementation of projects and programs that present strategies for information and dissemination of the possible side effects of this practice.